Orphan care a comparative view - Bailey, Joanne 1963- (Virginia Kumarian Press, 2012)
Orphan care; Care for children in Btswana; The care and shelter of children and adolescents in Brazil; Social service for orphans and its challenges in China...
Includes bibliographical references and index
Keywords: Orphans -- Social conditions -- Developing countries; Orphans -- Developing countries -- Services for; Orphans -- Developing countries -- Institutional care; Social work with children -- Developing countries; Chăm sóc trẻ mồ côi